2000
DOI: 10.1074/jbc.m007732200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C θ and ε Promote T-cell Survival by a Rsk-dependent Phosphorylation and Inactivation of BAD

Abstract: Both MAPK and protein kinase C (PKC) signaling pathways promote cell survival and protect against cell death. Here, we show that 12-O-tetradecanoylphorbol-13-acetate (TPA) prevents Fas-induced apoptosis in T lymphocytes. The effect of TPA was specifically abolished by the PKC inhibitor GF109203X and by dominant negative PKC, PKC⑀, and PKC␣, suggesting that novel and conventional PKC isoforms mediate phorbol ester action. Moreover, TPA stimulated phosphorylation of BAD at serine 112, an effect abrogated by GF10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(128 citation statements)
references
References 27 publications
8
119
1
Order By: Relevance
“…Surprisingly, higher doses of SB202190, which drastically increased JNK activity, were nevertheless found to inhibit megakaryocytic differentiation of K562 and to induce cell death more especially in the presence of PMA. The effect of the combination of PMA and high doses of SB may appear somewhat surprising since PMA has been consistently shown to protect various cell lines against apoptosis (Bertolotto et al, 2000;Villalba et al, 2001;Herrant et al, 2002). However, we have previously established that inhibition of the NFkB pathway, for example, can convert PMA from a death-protecting to a death-inducing function (Busuttil et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, higher doses of SB202190, which drastically increased JNK activity, were nevertheless found to inhibit megakaryocytic differentiation of K562 and to induce cell death more especially in the presence of PMA. The effect of the combination of PMA and high doses of SB may appear somewhat surprising since PMA has been consistently shown to protect various cell lines against apoptosis (Bertolotto et al, 2000;Villalba et al, 2001;Herrant et al, 2002). However, we have previously established that inhibition of the NFkB pathway, for example, can convert PMA from a death-protecting to a death-inducing function (Busuttil et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of constitutively active PKCε increased phosphorylation of Bad at Ser112 [130,136] but not Ser136 and inhibited CH11 (a FAS ligand mimic)-induced apoptosis in Jurkat T cells [130]. An interaction between PKCε and Bax was identified in CWR22 prostate tumor xenografts.…”
Section: Pkcε and Bcl-2 Family: Many Partners In The Dance Of Deathmentioning
confidence: 98%
“…Data supporting isoform-specific regulation of Bcl-2 family members are sparse, but quite consistent in that antiapoptotic PKCε enhances antiapoptotic Bcl-2 members [34,129] while inhibiting the proapoptotic members of the family [31,34,130,131]. Suzuki et al first reported that intense expression of Bcl-2 during the development of pregnancy-dependent mammary tumors (PDMTs) to malignant tumors was associated with overexpression of PKCε but not of other isozymes, such as PKCα, -δ, -η, -ζ or -λ [132].…”
Section: Pkcε and Bcl-2 Family: Many Partners In The Dance Of Deathmentioning
confidence: 99%
“…A clue may come from the existence of the 90 kDa Na þ /H þ exchanger 1 (NHE1) kinase (also known as p90 RSK ) that has been suggested to represent a common NHE1 regulator for diverse signaling pathways (reviewed by Karmazyn et al 12 ) and whose activation is blocked by tyrosine kinase inhibitors. 16 In this regard, it is worth noting that the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) has been recently reported to rescue T lymphocytes from Fas-mediated apoptosis via activation of p90 RSK , resulting in phosphorylation and inactivation of the proapoptotic protein BAD; 17 moreover, TPA has long been known to induce intracellular alkalinization via NHE activation in various cells (reviewed by Putney et al 11 and Karmazyn et al 12 ). In this context, one might then speculate that p90 RSK would be inactivated upon Fas ligation, possibly due to an SHP-1-dependent dephosphorylation step, leading to downregulation of NHE1 and hence development of acidification and apoptosis.…”
Section: Intracellular Acidification In Apoptosismentioning
confidence: 99%